2020
DOI: 10.21203/rs.3.rs-78194/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Osimertinib in Advanced EGFR-T790M Mutation-positive Non-small Cell Lung Cancer Patients Treated Within the Special Use Medication Program in Spain. OSIREX-spanish Lung Cancer Group

Abstract: Background: AURA study reported 61% objective response rate and progression-free survival of 9.6 months with osimertinib in patients with EGFR/T790M+ non-small cell lung cancer. Due to lack of real-world data, we proposed this study to describe the experience with osimertinib in Spain.Methods: Post-authorization, non-interventional Special Use Medication Program, multicenter, retrospective study in advanced EGFR/T790M+ non-small cell lung cancer. 155 patients were enrolled (August 2016-December 2018) from 30 s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In this context, the survival outcomes of other real-life studies varied between median 9.4 and 14.5 months of PFS, in the second-line treatment of advanced NSCLC with T790M mutation (9)(10)(11)(12)(13)(14). The Spanish Lung Cancer Group reported a median of 9.4 months PFS in 155 patients, and this was a very close to the PFS reported in the pivotal phase 3 trial (6, 10).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this context, the survival outcomes of other real-life studies varied between median 9.4 and 14.5 months of PFS, in the second-line treatment of advanced NSCLC with T790M mutation (9)(10)(11)(12)(13)(14). The Spanish Lung Cancer Group reported a median of 9.4 months PFS in 155 patients, and this was a very close to the PFS reported in the pivotal phase 3 trial (6, 10).…”
Section: Discussionmentioning
confidence: 60%
“…In our study, ORR was higher (82%) and DCR was similar with 95%. Studies from Europe already reported lower rates with approximately 40-50% of ORR (10,12). No data was indicating that the Turkish population might be more "sensitive" to this treatment than Western population.…”
Section: Discussionmentioning
confidence: 97%
“…This result is comparable to or even better than the results of previous retrospective real-world studies, which showed a PFS of 9.4 to 10.1 months and OS of 24 to 47.3 months for osimertinib as a second-line or subsequent treatment. (21)(22)(23) The better PFS and OS in this study may be due to the relatively small number of patients and the focus on only those treated with osimertinib as the second-line therapy.…”
Section: Discussionmentioning
confidence: 99%